2010
DOI: 10.1080/15421401003720066
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Stability of PPy Film on Ti by PEG Incorporation

Abstract: Composite films based on polypyrrole (PPy) and polyethylene glycol (PEG) were synthesized on titanium electrode, using various percentages of PEG, as the insulating material in order to enhance surface properties of the polymer composite films. The Fourier transform infrared spectroscopy (FT-IR) was performed to demonstrate the formation of a PPy-PEG composite film. The corrosion behaviour of coatings has been studied by Tafel tests and cyclic voltammetry. The PPy-PEG films=electrolyte interface was analyzed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…At high PEG concentration a decrease of bending displacement was observed [ 19 ]. Other research of PPy inclusion of PEG revealed that the hydrophilic characteristics increased [ 20 ] as well as discovery of a certain affinity of PEG to metallic cations rather than anions [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…At high PEG concentration a decrease of bending displacement was observed [ 19 ]. Other research of PPy inclusion of PEG revealed that the hydrophilic characteristics increased [ 20 ] as well as discovery of a certain affinity of PEG to metallic cations rather than anions [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve the surface characteristics of the Ti alloy/PPy electrode system, a composite PPy‐PEG film was electropolymerized on Ti6Al7Nb alloy in the presence of 4% PEG (400 molecular weight). This concentration of PEG was established after previous research on pure titanium 28, which showed that 3–4% PEG is optimal for obtaining the best electrochemical stability of PPy/PEG composite.…”
Section: Methodsmentioning
confidence: 99%
“…A polypyrrole/polyethylene glycol (PPy/PEG) composite coating was proposed for platinum [11], ITO [12], and titanium [13]. However, to the best of our knowledge, there is a lack of information about the deposition of PPy/PEG coating onto Mg alloys.…”
Section: Introductionmentioning
confidence: 99%